Coupled surface‐subsurface hydrologic measurements reveal infiltration, recharge, and discharge dynamics across the swash zone of a sandy beach. Issue 11 (6th November 2015) - Heiss, James W.; Puleo, Jack A.; Ullman, William J.; Michael, Holly A.
Abstract: Swash‐groundwater interactions affect the biogeochemistry of beach aquifers and the transport of solutes and sediment across the beachface. Improved understanding of the complex, coupled dynamics of surface and subsurface flow processes in the swash zone is required to better estimate chemical fluxes to the sea and predict the morphological evolution of beaches. Simultaneous high‐frequency measurements of saturation, water table elevation, and the cross‐shore locations of runup and the boundary between the saturated and unsaturated beachface (surface saturation boundary) were collected on a sandy beach to link groundwater flow dynamics with swash zone forcing. Saturation and lysimeter measurements showed the dynamic response of subsurface saturation to swash events and permitted estimation of infiltration rates. Surface and subsurface observations revealed a decoupling of the surface saturation boundary and the intersection between the water table and the beachface. Surface measurements alone were insufficient to delineate the infiltration and discharge zones, which moved independently of the surface saturation boundary. Results show for the first time the motion and areal extent of infiltration and recharge zones, and constrain the maximum size of the subaerial discharge zone over swash and tidal time scales. The width of the infiltration zone was controlled by swash processes, and subaerial discharge was controlled primarily by tidal processes. These dynamics reveal the tightly coupled nature of surface and subsurface processes over multiple time scales, with implications for sediment transport and fluid and solute fluxes through the hydrologically and biogeochemically active intertidal zone of sandy beaches. Key Points: Infiltration and recharge zones on the beachface varied temporally and spatially Steady unsaturated recharge to the aquifer occurred at swash and tidal time scales Subsurface observations are needed to delineate infiltration and discharge zones